Conflict and negotiation in the early church : letters from late antiquity, translated from the Greek, Latin, and Syriac - Allen, Pauline, 1948-; Neil, Bronwen (The Catholic University of America Press, 2020)
"A systematic study of the role of the bishop in negotiating conflict within the church in the Mediterranean world of the seventh century, based on letters translated from Latin, Greek, and Syriac"--